STUDI PENGARUH WAKTU TINGGAL TERHADAP PENYISIHAN PARAMETER BOD5, COD DAN TSS LINDI MENGGUNAKAN BIOFILTER SECARA ANAEROB-AEROB (Studi Kasus: TPA Ngronggo, Kota Salatiga, Jawa Tengah) - Bernadette Nusye Parasmita (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
Ngronggo landfill which classified as young landfills is young are less than 10 years old so it still has a high organic content. So it needs some treatment system to treat leachate which generated by the waste degradation process so it does not pollute the environment. In this study the parameters that will be examined are the Biochemical Oxygen Demand (BOD5), Chemical Oxygen Demand (COD) and Total Suspended Solid (TSS). Biofilter treatment used is a combination of aerobic to anaerobic. In this research, variations in time detention to obtain the greatest removal efficiency. Additionally, it also will be seen how the differences between each of the processing efficiency of pollutant removal parameters based on variations in the time detention for BOD5 reached 65%, reaching 29.21% for COD and TSS reached 39.50%. The results of these three parameters occurred at the longest time detention, ie 25 hours for anaerobic biofilter and 17.5 hours for aerobic biofilter. Therefore it can be said that the longer residence time in the biofilter treatment processes, the greater the value of removal efficiency that occurs in the BOD5, COD and TSS.